Avaliação visual da estrutura do solo aplicada a solos argilosos - Pacheco, Vacilania (2024)
Visual Evaluation of Soil Structure (VESS) was developed in temperate soils and, although it is already widely used in tropical and subtropical soils, the different climatic and pedological scenarios are an incentive for refinements and testing of the method, especially in soils with high clay content. In this thesis, two experiments were developed with the following objectives: (1) to identify whether soil resistance or porosity is the determining factor for management changes, when assigning SqVESS scores of 4 in clayey tropical soils of basaltic origin under consolidated no-tillage (NT) system; (2) to evaluate whether there is a spatial dependence relationship between VESS and its relationship with physical attributes and OM, pointing out possible correlations with VESS, in a clayey Cambisol under NT. For the first experiment, VESS method evaluations were performed on clayey soils classified as Latosols, under NT, collected in four locations: three in the state of Paraná and one in Scotland (Cauldside), adopted as a control treatment, where the method was originally developed. Evaluations were performed using the VESS method and undisturbed soil samples were collected to determine soil bulk density, macro, micro and total porosity, soil penetration resistance (PR) and soil air permeability (Ka) in soil with SqVESS ≥ 4. For macroporosity and Ka, the differences were compared between Cauldside and Brazilian soils by confidence interval (p<0.05), while for the other attributes the differences were discussed by descriptive statistics and relative values. The macroporosity and Ka values compared with the reference soil (Cauldside) demonstrate that the areas of Brazil presented better average values, however, in conditions of high water content all soils would present limiting conditions for plant development. The PR curves showed that the values of soil water content and bulk density, in which PR can potentially cause physical restrictions for the root system, for all soils are very close to the field capacity, indicating that the visible porosity observed in SqVESS 4 in areas under NT does not necessarily represent that the soil has functional porosity, therefore RP is the main attribute to be considered, maintaining the management decision indicated in the chart. For the second experiment, the tests were carried out in a clayey Cambisol Haplic, cultivated with oats in the municipality of Mariópolis - Paraná, having been established a 100x100 m (10.000 m2 ) grid, subdivided into 52 points, where VESS, physical attributes and organic matter evaluations were carried out, enabling geostatistical analysis. For the attributes that indicated spatial dependence, in their experimental semivariograms, kriging was used to interpolate estimates of locations between the sampling points, creating contour plots. The VESS presented spatial dependence (22.5 m), as well as the attributes total porosity (94.3 m) and PR (68.7 m). The cross semivariograms showed that there was no correlation between the attributes that presented spatial dependence, however the quantitative properties were able to bring to light localized variations that affect specific aspects of soil quality.